Modified Cascaded Five Level Multilevel Inverter Using Hybrid Pulse Width Modulation - Bakshi, Saket; Katkar, Nishita; Hadkar, Malini; Suryavanshi, Sanyogita; Swapna, J (International Journal of Computer Sciences and Engineering, 2025)
Multilevel inverter is an effective and practical solution for increasing power demand and reducing harmonics of AC waveforms. Such inverters synthesize a desired output voltage from several levels of dc voltages as inputs. Our aim in this project is to analyze the performance of cascaded five level inverter using hybrid pulse width modulation technique. It has been found that this technique reduces the switching losses and total harmonic distortion. In the conventional cascaded H-bridge multilevel inverter eight power switches have been used is reduced to six power switches by employing this topology and it can be employed for high voltage and high power applications. Due to these advantages, cascaded H-bridge inverter has been widely applied to such applications as HVDC, SVC, stabilizers, and high power motor drives. The performance can be analyzed by the MATLAB/Simulink.